Perceived quality and intention to revisit coffee concept shops in Malaysia: A mixed-methods approach - Hiram, Ting; Wee, Ming Lau; Cheah, Jun-Hwa; Yusman, Yacob; Mumtaz Ali, Memon; Lau, Evan (Emerald Publishing Limited, 2018)
Purpose – The purpose of this paper is to examine the effect of perceived quality on intention to revisit coffee concept shops among regular and irregular consumers. Specifically, the framework developed by Pine and Gilmore (2000) is adopted to look into the effect of product, service and experience qualities on intention to revisit. Design/methodology/approach – The explanatory sequential mixed-methods design was used to articulate the intention of consumers to revisit coffee concept shops. A preliminary study was conducted to define regular and irregular consumers. Self-administered questionnaire was first administered before using interview to elicit more insights and triangulate the findings. Findings – The combination of both quantitative and qualitative findings show that the experiences of regular consumers at coffee concept shops include personal routine activities, while the experiences of irregular customers are composed of occasions with specific and collective purposes. While the intention to revisit of the former is related to the product and service quality, the intention of the latter is largely affected by its service and experience quality. Originality/value – Given the rapid rise of coffee concept shops in the developing markets, the use of a mixed-methods design provides more insights into the intention to revisit of the regular and irregular consumers. It underscores the importance for the organisations to know what really matters to the diverse consumers.